Auditory Event-related Potentials in Children With Attention Deficit Hyperactivity Disorder - Min-Lan Tsai; Kun-Long Hung; Hui-Hua Lu (Pediatrics and Neonatology)
Recording of event-related potentials (ERPs) from the scalp is a noninvasive technique reflecting the sensory and cognitive processes associated with attention tasks. Attention deficit hyperactivity disorder (ADHD) is a disorder involving deficits in attention and behavioral control. The aim of this study was to investigate the difference in ERPs between normal children and those with ADHD. Methods: We examined 50 children with ADHD and 51 age-matched controls. All children with ADHD met the full criteria for ADHD according to Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV). The auditory oddball paradigm was applied, and event-related long-latency components (N1, P2, N2 and P3) from Fz, Cz and Pz were measured in each test subject. Results: Children with ADHD showed a significantly longer latency and a lower amplitude of P3 compared to normal control children (p < 0.01). Delayed N2 latency at the Pz electrode was shown in children with ADHD compared to normal controls (p < 0.01). No differences in other ERP indices were found between children with ADHD and controls. When divided into four age groups, the latency of P3 was significantly increased in all age groups and a significantly smaller amplitude in P3 over the central region was found in children with ADHD > 10 years of age (p < 0.05). Conclusion: We found that the endogenous ERPs (P3 and N2) were significantly affected in children with ADHD, compared to exogenous ERPs (N1 and P2). Increased latency of P3 suggests a slower processing speed, and decreased P3 amplitude is interpreted as disruption of inhibitory control in children with ADHD. These results indicate a neurocognitive abnormality in ADHD, as presented by a reduction in ERP response.